PELUANGNYA MENINGKATKAN EKONOMI DAERAH MELALUI PARIWISATA HALAL (ISLAMIC CENTRE) - Supriadi, Herman; Arfani, Egi Septi Putra; Ramli, Muhammad (STKIP Persada Khatulistiwa Sintang, 2024)
This research aims to find the potential and prospects for halal tourism in the city of Mataram, and what facilities support the Islamic Center destination in the city of Mataram and what the strategy of the Mataram city government is to improve the economy in the city. The type of research used by is the descriptive method with a qualitative approach. The data source used is primary data obtained directly through observation, interviews and documentation. The data analysis techniques used are data collection, data reduction, presentation and drawing conclusions. The research results show that the Islamic Center Mosque in Mataram City is considered to have great potential in improving the economy of Mataram City. As well as the prospects that can be utilized by halal tourism in the city of Mataram which are very adequate in supporting the implementation of halal tourism, namely the Islamic Center Mosque in Mataram City is considered to be one of the most attractive destinations and plays an important role in improving the regional economy of Mataram City in various aspects. Its role not only to increase the income of people who live in Mataram but also those who live out in other Regency.